Refugee Movements from the Sudan: An Overview Analysis - Otunnu, Ogenga (Refuge: Canada’s Journal on Refugees, 1994)
Most refugees do not leave their home with a national passport in hand. Nor do they have prepaid tickets for their transport since they do not take national airlines or railways when they leave their countries. They leave in acute situations and for many of them their journey is hampered by acute problems. They flee in disguise, avoid the main roads; and are ignorant of what lies ahead since they travel through unknown territory often without guide. This makes flight for many a grope for safety in total darkness. And such flight is filled with numerous hardships and danger. (Bulcha, M. 1988. Flight and Integration: Causes of Mass Exodus from Ethiopia and Problems of Integration in the Sudan. Uppsala: Scandinavian Institute of African Studies, 138.)